DIALEKTIKA ELITE PESANTREN DALAM PENGEMBANGAN KURIKULUM LOKAL MADRASAH DI PESANTREN NURUL ISLAM 1 DAN AL-QODIRI 1 JEMBER - Fauzi, Imron (Ta'allum: Jurnal Pendidikan Islam, 2019)
This study examines the elite dialectics of Nurul Islam 1 and Al-Qodiri 1 Jember Islamic Boarding School (pesantren) in developing their local curriculum. This study uses qualitative method. A number of data are collected through interview, observation, and documentary techniques. In analyzing the data, researcher uses data reduction, data display, and then find a conclusion. The researcher uses  triangulation method in validating the data. The result of this study shows that the dialectics conducted by elites pesantren in developing local curriculum significantly developed through complementary dialogic way without changing national curriculum as well. The alternative ways in responding supervision and accreditation from the government, they made/served two forms of curriculum, namely national curriculum or government version curriculum and local curriculum or pesantren version curriculum. The dialectic inhibition factor is a guideline that still unclear, causes miscommunication in implementing it; local curriculum evaluates independently; and a complicated division of learning schedule, between activities in pesantren, curricular activities, and extracurricular activities at madrasah.